ALAT PERAGA PROSES FERTILISASI UNTUK MENINGKATKAN HASIL BELAJAR, MOTIVASI DAN AKTIVITAS SISWA DI MTsN 1 BANDA ACEH - Nurmahni Harahap (Jurnal Dedikasi Pendidikan, 2020)
Education is one of the most important factors in improving human resources. In the process of improving the quality of human resources integrated education with the process of improving the quality of human resources. One of the efforts in improving the quality of education is the development of curriculum and learning innovation. In the learning process requires educational aids whose use is integrated with the objectives and content or subject matter to optimize the achievement of defined teaching objectives. This study aims to determine the improvement of learning outcomes, motivation and student learning activities with the use of props fertilization. The method used in this study is an experimental method. The research was conducted in MTsN 1 Banda Aceh science laboratory. The research data is taken on Agust 01 s/d 15, 2018. The instrument in this research is about test results of the study, questionnaire of student motivation and observation sheet of student learning activity. data analysis in this research uses a descriptive statistic that is a percentage. The results of this study are the use of fertilization tool can improve learning outcomes, motivation, and student learning activities